Shape of Earth's lithosphere and geotectonics - Tserklevych, A.L.; Shylo, Y.A. (Reports of the National Academy of Sciences of Ukraine, 2018)
The studies of the computer simulation results of the Earth lithosphere figure reorientation allow revealing the certain regularities reflecting structure-forming processes. It has been shown that the shape of the lithosphere surface has a different orientation relative to the geoid figure. The acting horizontal forces in the upper shell of the planet are calculated, introducing the concept of “evolutionary deviation of a plumb” and assuming that the tangential forces are proportional to the angle, which is defined as the angle between the direction of the plumb line in the past geological epoch and the plumb line direction at a given point. The calculated fields of tangential force vectors show a good consistency with the directions of the space-time displacements of Earth's continents and tectonic plates and consistent with the results of the horizontal movements of GNSS stations. This is a quite convincing evidence that, under the long-term action of vortex rotational-gravitational forces, the lithospheric masses acquire the property of creep.